(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2018)
Research on employee satisfaction has shown that there is a positive correlation between the level of employee job satisfaction on one hand and job performance and quality service delivery on the other. Alternately put, the higher the level of employee job satisfaction, the higher the job performance and the greater the quality service delivery, and vice versa.This paper investigates job satisfaction among employees in the hospitality industry, specifically in a two-star Coconut Grove hotel. Data for the study were collected from a judgmental and simple random sample of 90 guests and 23 members of staff and management of Coconut Grove, respectively. The study revealed that the hotel management and staff expressed satisfaction with their jobs due to a number of reasons. Significant among them were that, they were involved in decision making processes within the establishment, and that, they (members of staff) were motivated to function as managers. In addition, management took the necessary steps as much as possible to meet the needs of workers by way of remuneration. Finally, the research findings revealed that job satisfaction indeed constitutes a gateway to quality service delivery in the hospitality industry. Thus, in order to enhance job performance, the study recommends that the needs of employees which are important service culture requirementsmust be met so as to enable them (staff) work efficiently and effectively.